2014
DOI: 10.1002/smll.201401342
|View full text |Cite
|
Sign up to set email alerts
|

Energy Upconversion in GaP/GaNP Core/Shell Nanowires for Enhanced Near‐Infrared Light Harvesting

Abstract: Semiconductor nanowires (NWs) have recently gained increasing interest due to their great potential for photovoltaics. A novel material system based on GaNP NWs is considered to be highly suitable for applications in efficient multi-junction and intermediate band solar cells.This work shows that though the bandgap energies of GaN x P 1-x alloys lie within the visible spectral range (i.e. within 540 -650 nm for the currently achievable x< 3%), coaxial GaNP NWs grown on Si substrates can also harvest infrared li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 45 publications
1
30
0
Order By: Relevance
“…Recently we have shown that these functionalities can be further enhanced in the case of nanowires. For example, the light harvesting efficiency of GaNP NW arrays can be improved via energy upconversion caused by two-step two photon absorption [15].…”
mentioning
confidence: 99%
“…Recently we have shown that these functionalities can be further enhanced in the case of nanowires. For example, the light harvesting efficiency of GaNP NW arrays can be improved via energy upconversion caused by two-step two photon absorption [15].…”
mentioning
confidence: 99%
“…8 A promising material system attractive for applications in solar cells and light-emitting diodes is GaN x P 1-x / GaN y P 1-y core/shell NWs. [9][10][11][12] Incorporation of several percent of nitrogen in gallium phosphide reduces its lattice constant, thereby minimizing lattice mismatch with Si. 13 Also, a strong interaction between the N-related localized states and the extended states of GaP modifies the band structure of the forming alloy leading to an increased oscillator strength of the band-to-band optical transitions [14][15][16] and a splitting of the conduction band states into two subbands.…”
mentioning
confidence: 99%
“…There are in principle several possible physical mechanisms that could lead to this PL enhancement. The first possibility is that P2 with a below-bandgap photon energy could generate free electrons and holes via defect-mediated upconversion or two-photon nonlinear processes, 35,36 leading to enhanced PL emissions. This possibility is not plausible here because photo-excitation with only the NIR light P2 did not result in any sizable PL emissions.…”
Section: Seriesmentioning
confidence: 99%